2021
DOI: 10.1002/cl2.1140
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: Involving men and boys in family planning: A systematic review of the effective components and characteristics of complex interventions in low‐ and middle‐income countries

Abstract: BACKGROUND | The problemFamily planning (FP) helps people avoid unintended pregnancy, attain their desired number of children and/or determine the spacing of pregnancies. Effective FP is achieved through the use of contraceptive methods, provision of safe abortion, and prevention and treatment of infertility. FP also contributes to reduced maternal, neonatal and child morbidity and mortality, as well as the negative economic and psychosocial implications that unintended pregnancy, pregnancy complications and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…It aims at improving family lives and contributing to sustainability efforts at both the micro and macro levels. FP is a method of population control and enhances the reduction of unplanned pregnancies by providing direct or indirect benefits, such as lowered maternal morbidity and mortality [ 5 , 6 ], increased educational and employment opportunities for women who are able to delay childbirth [ 7 , 8 ], decreased use of unsafe abortion methods [ 9 ], reduced risk of HIV transmission to unborn children [ 10 , 11 ], and lowered neonatal, infant, and child mortality [ 12 ]. According to the World Health Organization (WHO) [ 13 ], after years of concerted work, a significant proportion of women worldwide wish to avoid getting pregnant, but neither they nor their partners are using contraceptives.…”
Section: Introductionmentioning
confidence: 99%
“…It aims at improving family lives and contributing to sustainability efforts at both the micro and macro levels. FP is a method of population control and enhances the reduction of unplanned pregnancies by providing direct or indirect benefits, such as lowered maternal morbidity and mortality [ 5 , 6 ], increased educational and employment opportunities for women who are able to delay childbirth [ 7 , 8 ], decreased use of unsafe abortion methods [ 9 ], reduced risk of HIV transmission to unborn children [ 10 , 11 ], and lowered neonatal, infant, and child mortality [ 12 ]. According to the World Health Organization (WHO) [ 13 ], after years of concerted work, a significant proportion of women worldwide wish to avoid getting pregnant, but neither they nor their partners are using contraceptives.…”
Section: Introductionmentioning
confidence: 99%
“…Suggestions on improving family planning include involving men. 60 Unplanned pregnancies were also associated in South Africa with antenatal depression, which is one of the strongest predictors of postnatal depression. 61 Multivariate analysis in the current study showed that support from partners or husbands was associated with the decreased odd of having PND than those who did not receive support.…”
Section: Discussionmentioning
confidence: 99%
“…Suggestions on improving family planning include involving men. 60 Unplanned pregnancies were also associated in South Africa with antenatal depression, which is one of the strongest predictors of postnatal depression. 61 …”
Section: Discussionmentioning
confidence: 99%
“…More information on the review design and methodology is available in the review protocol [ 19 ]. This rapid review was conducted as part of an ongoing systematic review that aims to identify the effective components and characteristics of interventions involving men and boys in LMICs in family planning [ 20 ].…”
Section: Methodsmentioning
confidence: 99%